SIMULASI JALUR EVAKUASI UNTUK BENCANA TSUNAMI BERBASIS DATA PENGINDERAAN JAUH (STUDI KASUS: KOTA PADANG, PROPINSI SUMATERA BARAT) - Trisakti, Bambang; Carolita, Ita; Nur, Mawardi (Institut Teknologi Sepuluh Nopember, 2007)
Tsunami disaster caused great damages and very large victims especially when occurs in urban area along. Therefore information of evacuation in a map is very important for disaster preparedness in order to minimize the number of victims in affected area. Here, information generated from remote sensing satellite data (Landsat, SPOT-5 nad DEM) and secondary data (administration boundary and field survey data) are used ti simulate evacuation route and to produce a map for Padang City. Vulnerability and evacuation areas are determined based on information of maximum tsunami height in shoreline and topography condition. Landuse/landcover and infrastructure (road, bridge and building) are extracted from SPOT data. All the data obtained from remote sensing and secondary data are integrated using geospatial modeling to simulate tsunami evacuation routes. The simulation of evacuation route in Padang City for tsunami preparedness is provided by considering river line, shelters and save zone, available infrastructur (road), the shortest distance (to shelters and save zone) and local community experiences.